Wound botulism caused by Clostridium subterminale after a heroin injection - Paris A. Cook; Aimee Mishler; Dan Quan; Ashley Parrish-Garcia (MDPI AG, 2018)
Botulism is caused by toxin production from many species of Clostridium, most commonly Clostridium botulinum as well as C. baratii and C. butyricum. Development of wound botulism is associated with injection drug users but has also been described in traumatic injuries with exposure to soil. A patient presented to the emergency department with a complaint of descending, progressive weakness. He recently reported skin popping with heroin injections. Heptavalent botulinum antitoxin was obtained from the [Center for Disease Control and Prevention (CDC)]. On hospital day seven, the anaerobic wound cultures resulted with growth of Clostridium subterminale.